Impact of N fertilization on subsoil properties - Schön, Martina (2011)
During the last century mankind has been able to boost food production with fertilization and improved cultivation techniques. Crop biomass production has been increased both, above and below ground. Due to this fact it is expected that highly yielding crops may also influence the soil organic carbon pool in the subsoil through increasing root production. The goal of this thesis was to investigate the impact of low and high yields (no N vs high N fertilization) on (1) the soil organic matter pool (2) soil stability and (3) related chemical and physical interactions.